ETSI activities on next generation networks - Julien, Christian (Communications - Scientific letters of the University of Zilina, 2004)
The contribution deals with the current activities in ETSI (European Telecommunications Standards Institute) on Next Generation Networks (NGN). The first part includes the general information on ETSI and the creation of the new Technical Committee TISPAN (Telecommunications and Internet converged Services and Protocols for Advanced Networks) which is responsible for all aspects of the wired networks like signalling protocols or systems interworking and which is currently moving towards definition and specification of the NGN. The next part is aimed at the current structure of the TC TISPAN and finally, the key objectives within the TISPAN Releases are presented.